Boxplot graph analysis with triangular and trapezoidal fuzzy numbers - Boria Reverter, Sefa; Gil Lafuente, Anna María; Torres Martínez, Agustín (2021)
Decision making under conditions of uncertainty is one of the most recurrent problems of the present, in a highly changing environment with little margin to obtain complete and accurate information, that allows to know in depth the behavior of the variables when analyzing the problems. In many cases we have data that are vague, imprecise or incomplete and, consequently, it is difficult to establish the probability of occurrence. Since, it arises fuzzy logic (Zadeh, 1965).